CCN2 is necessary for adhesive responses to transforming growth factor-beta1 in embryonic fibroblasts. - Shi-wen, X; Stanton, L; Kennedy, L; Pala, D; Chen, Y; Howat, S; Renzoni, E; Carter, D; Bou-Gharios, G; Stratton, R; Pearson, J; Beier, F; et al. (2006)
CCN2 is induced by transforming growth factor-beta (TGFbeta) in fibroblasts and is overexpressed in connective tissue disease. CCN2 has been proposed to be a downstream mediator of TGFbeta action in fibroblasts; however, the role of CCN2 in regulating this process unclear. By using embryonic fibroblasts isolated from ccn2-/- mice, we showed that CCN2 is required for a subset of responses to TGFbeta. Affymetrix genome-wide expression profiling revealed that 942 transcripts were induced by TGFbeta greater than 2-fold in ccn2+/+ fibroblasts, of which 345 were not induced in ccn2-/- fibroblasts, including pro-adhesive and matrix remodeling genes. Whereas TGFbeta properly induced a generic Smad3-responsive promoter in ccn2-/- fibroblasts, TGFbeta-induced activation of focal adhesion kinase (FAK) and Akt was reduced in ccn2-/- fibroblasts. Emphasizing the importance of FAK and Akt activation in CCN2-dependent transcriptional responses to TGFbeta in fibroblasts, CCN2-dependent transcripts were not induced by TGFbeta in fak-/- fibroblasts and were reduced by wortmannin in wild-type fibroblasts. Akt1 overexpression in ccn2-/- fibroblasts rescued the TGFbeta-induced transcription of CCN2-dependent mRNA. Finally, induction of TGFbeta-induced fibroblast adhesion to fibronectin and type I collagen was significantly diminished in ccn2-/- fibroblasts. Thus in embryonic fibroblasts, CCN2 is a necessary cofactor required for TGFbeta to activate the adhesive FAK/Akt/phosphatidylinositol 3-kinase cascade, FAK/Akt-dependent genes, and adhesion to matrix.